Long-chain fatty acid β-oxidation regulates embryonic development by H3K18 acetylation in mice - Zheng, Kefan; Cui, Hongdi; Tang, Ziheng; Song, Entong; Kong, Qingran; Zhang, Jiaming; Li, Hao; Zhao, Qi (Frontiers in Cell and Developmental Biology, 2025)
Fatty acids are not only important as energy sources, but also playing crucial roles in maintaining cellular homeostasis. However, their role in preimplantation development remains unclear. Here, we find that fatty acids gradually accumulate after 4-cell stage in mouse preimplantation development. And, the expressions of fatty acid degradation-related genes are increased along the developmental process. Inhibition of long-chain fatty acid β-oxidation (LCFAO) results in preimplantation developmental arrest, downregulated expressions of S phase-related genes, and loss of H3K18ac modification. By profiling the landscape of H3K18ac, we show that H3K18ac is enriched on the promoter regions of S phase-related genes and correlates with their expression. Together, these findings suggest that LCFAO regulate mouse preimplantation development through H3K18ac, providing additional evidence for metabolic-epigenetic crosstalk in embryonic development.